The economic reintegration of former colonial residents in postwar Japan - Ivings, Steven (The economic and business history of occupied Japan, 2017)
The process of repatriation itself and the often tragic personal accounts of the struggles of 'repatriates' to return to Japan have gained a degree of scholarly
Gesehen am 07.07.2020